Potential impact of HercepTest™ mAb PharmDx (Dako Omnis) (ge001) in breast cancer diagnosis - Andrzej Marszałek; Agata Kubicka; Inga Jagiełło; Anna Malicka-Durczak (Polish Journal of Pathology, 2023)
The HER2 gene is a biomarker for breast cancer prognosis and treatment. Overexpression of HER2 protein determined by immunohistochemistry (IHC) or amplification of the HER2 gene determined by fluorescence in situ hybridization (FISH) is a condition for qualifying patients for anti-HER2 therapy. Due to the high toxicity of anti-HER2 treatment, proper patient selection is essential. In our study we compared 40 cases with IHC staining of HER2 antibody determined by Ventana PATHWAY anti-HER2/neu antibody (4B5) as HER2 2+ with the new antibody (HercepTest™ mAb PharmDx [Dako Omnis] [GE001]). Then using a double-blind study we compared the (IHC) evaluation with FISH results. In 65% of cases (26/40) the IHC 2+ score remained unchanged, in 32.5% of cases (13/40) expression of HER2 protein after IHC with new antibody was indicated as 3+ score, and in one case we observed a decrease of HER2 protein expression to 1+. In all cases but one, in which we found IHC HER 3+ with new antibody, there was FISH amplification. We have reason to believe that the new antibody will reduce the diagnostic time and avoid unnecessary costs. Due to the small study group, further investigation is needed.